2015
DOI: 10.1049/mnl.2014.0651
|View full text |Cite
|
Sign up to set email alerts
|

Combining surface effects and non‐local two variable refined plate theories on the shear/biaxial buckling and vibration of silver nanoplates

Abstract: In this reported work, surface effects and non-local two variable refined plate theories are combined on the shear/biaxial buckling and vibration of rectangular nanoplates. A silver sheet is selected as the case study to investigate the numerical results. Surface effects are considered by Gurtin-Murdoch's theory. The differential quadrature method is used to solve the governing equations. Differential quadrature solutions are verified by Navier's method. The influences of the non-local parameter on the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Various nonlocal plate models such as the Kirchhoff plate theory [250][251][252][253][254], first-order shear deformation model [55,255], two-variable refined theory of plates [256,257] and higher-order shear deformation model [258][259][260] have been employed so as to examine the linear vibration of nanoscale plates. On the other hand, to solve the size-dependent differential equations of these nonlocal plate models, different solution methods such as analytical approaches [261][262][263],…”
Section: 4d Size-dependent Vibration Of Nanoplatesmentioning
confidence: 99%
“…Various nonlocal plate models such as the Kirchhoff plate theory [250][251][252][253][254], first-order shear deformation model [55,255], two-variable refined theory of plates [256,257] and higher-order shear deformation model [258][259][260] have been employed so as to examine the linear vibration of nanoscale plates. On the other hand, to solve the size-dependent differential equations of these nonlocal plate models, different solution methods such as analytical approaches [261][262][263],…”
Section: 4d Size-dependent Vibration Of Nanoplatesmentioning
confidence: 99%
“…The buckling problems of simply supported nanoplates were analyzed by Wang and Wang [23] considering both non-local elasticity and surface effects. Karimi et al [24] investigated vibration, shear and biaxial buckling of rectangular nanoplates, by using the non-local two variable refined plate theory. Daneshmehr et al [25] studied the free vibration problems of functionally graded nanoplates via non-local elasticity and high order theories.…”
Section: Introductionmentioning
confidence: 99%
“…∂x∂y dxdy (24) where N, M and Q are the resultant forces, moments and shear forces, respectively. They are defined by:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the piezoelectric effect had a tendency to increase the stiffness of the plate, and vice versa for the magnetostrictive effect. Karimi et al (2015a) investigated surface effects and non-local two variable refined plate theories that were combined on the shear/biaxial buckling and vibration of rectangular nanoplates. Their results showed that by increasing the non-local parameter, the effects of surface on the buckling and vibration increased.…”
Section: Introductionmentioning
confidence: 99%